2013
DOI: 10.1021/bc4002689
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Production of Peptide C-Terminal α-Amides Using an Engineered Intein

Abstract: Peptides are of increasing interest as therapeutics in a wide range of diseases, including metabolic diseases such as diabetes and obesity. In the latter, peptide hormones such as peptide YY (PYY) and pancreatic peptide (PP) are important templates for drug design. Characteristic for these peptides is that they contain a C-terminal that is α-amidated, and this amidation is crucial for biological function. A challenge is to generate such peptides by recombinant means and particularly in a production scale. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 53 publications
0
29
0
1
Order By: Relevance
“…The evolved 202–08 intein did not appear to affect cleavage efficiency compared with the wild-type intein, and these cleavage efficiencies are consistent with those observed for bacterially produced proteins. 7 , 16 , 53 Furthermore, the release could possibly be enhanced by optimizing the carboxy-terminal residue of the target protein, which has previously been shown to impact the cleavage efficiency. 53 , 54 Regardless, the small amount of uncleaved material is not chemically functionalized and would not impact many downstream applications like antibody immobilization, but the uncleaved material could be removed by depletion via histidine tag purification if desired.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evolved 202–08 intein did not appear to affect cleavage efficiency compared with the wild-type intein, and these cleavage efficiencies are consistent with those observed for bacterially produced proteins. 7 , 16 , 53 Furthermore, the release could possibly be enhanced by optimizing the carboxy-terminal residue of the target protein, which has previously been shown to impact the cleavage efficiency. 53 , 54 Regardless, the small amount of uncleaved material is not chemically functionalized and would not impact many downstream applications like antibody immobilization, but the uncleaved material could be removed by depletion via histidine tag purification if desired.…”
Section: Discussionmentioning
confidence: 99%
“…This smaller intein variant led to a 1.2-fold increase in intein-peptide fusion production in E. coli . 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, no autocleavage was observed when the −1 residue was mutated to Phe and more limited autocleavage was observed for Gln. It has previously been reported that engineering inteins for a particular property can lead to unexpected changes in cleavage efficiency and behavior, therefore it is possible that the engineering of 202‐08 for increased secretion led to a more promiscuous cleavage behavior. Although autocleavage was limited when using the wild‐type intein compared with the 202‐08 intein, total secretion levels of the protein‐intein fusion were considerably lower for the wild‐type intein, similar to values reported previously .…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The secreted product can then be assayed with an anti-FLAG tag Western blot to identify the fraction of produced protein that has undergone successful cleavage. As intein cleavage efficiency and specificity are often difficult to predict, [26][27][28] and mutations to the Mxe GyrA intein can potentially affect intein cleavage activity, 26,29,30 the effects of −1 residue substitution were also screened for the presence of undesirable cleavage events that occur in the absence of MESNA (termed autocleavage). These could occur within the yeast secretory pathway or in the culture medium.…”
Section: Effects Of the −1 Residue On Intein Cleavagementioning
confidence: 99%